Modeling the distribution of Norway rats (Rattus norvegicus) on offshore islands in the Falkland Islands - Tabak, Michael A.; Poncet, Sally; Passfield, Ken; Martinez del Rio, Carlos (NeoBiota, 2015)
Non-native rats (Rattus spp.) threaten native island species worldwide. Efforts to eradicate them from islands have increased in frequency and become more ambitious in recent years. However, the long-term success of some eradication efforts has been compromised by the ability of rats, particularly Norway rats (Rattus norvegicus) which are good swimmers, to recolonize islands following eradications. In the Falkland Islands, an archipelago in the South Atlantic Ocean, the distance of 250 m between islands (once suggested as the minimum separation distance for an effective barrier to recolonization) has shown to be insufficient. Norway rats are present on about half of the 503 islands in the Falklands. Bird diversity is lower on islands with rats and two vulnerable passerine species, Troglodytes cobbi (the only endemic Falkland Islands passerine) and Cinclodes antarcticus, have greatly reduced abundances and/or are absent on islands with rats. We used logistic regression models to investigate the potential factors that may determine the presence of Norway rats on 158 islands in the Falkland Islands. Our models included island area, distance to the nearest rat-infested island, island location, and the history of island use by humans as driving variables. Models best supported by data included only distance to the nearest potential source of rats and island area, but the relative magnitude of the effect of distance and area on the presence of rats varied depending on whether islands were in the eastern or western sector of the archipelago. The human use of an island was not a significant parameter in any models. A very large fraction (72%) of islands within 500 m of the nearest potential rat source had rats, but 97% of islands farther than 1,000 m away from potential rat sources were free of rats.